Penerapan Exprom II Dalam Menentukan Gabungan Kelompok Tani Terbaik Tingkat Kabupaten - Mesran Mesran; Kurnia Ulfa; Royanti Manurung (PETIR, 2019)
In this study the authors used a decision support system by applying the Extended Promethee II (EXPROM II) method to determine the best farmer group combinations at the Deli Serdang Agriculture Service. This method is a development of the Promethee II method that can calculate the distance difference between pairs of alternatives so as to produce an output that is ranking alternatives based on the highest net flow value. It is expected that the results of this study the authors can provide solutions to solving problems faced by the Department of Agriculture to solve the problem of determining the best combination of farmer groups objectively and more effectively by implementing a decision support system.